Unexpected placenta accreta spectrum in a primigravida with an unscarred uterus: life-threatening hemorrhage following vaginal delivery - Barakat, Hassan; Hamieh, Fatima; Barakat, Fatima; Awala, May; Habib, Khaled; Naufal, Naufal; Yared, Georges (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Placenta accreta spectrum disorders (PASD) are severe obstetric conditions associated with significant maternal and fetal morbidity. While the incidence of PASD has risen in correlation with increasing cesarean section rates, its occurrence in an unscarred uterus is exceptionally rare. We report a case of placenta increta in a 20-year-old primigravida with no identifiable risk factors. The diagnosis was made following a term vaginal delivery that was complicated by a retained placenta and subsequent life-threatening postpartum hemorrhage. This case is distinctive for its occurrence in a primigravida, contrasting with the few reported cases in unscarred uteri that are often described in multiparous women with a prior vaginal delivery. It underscores that PASD, while unlikely, can present in low-risk populations with no obstetric history. This report highlights the critical importance of maintaining a high index of suspicion and considering routine prenatal screening for radiological signs of PASD, even in low-risk populations.